การวิเคราะห์ความต้องการแรงงานในเชิงคุณภาพของสถานประกอบการอุตสาหกรรมในจังหวัดชลบุรีเมื่อมีการเปิดเสรีประชาคมเศรษฐกิจอาเซียน: Analysis of Demand for Qualitative Labor of Industrial Sector in Chonburi Province under Liberalization of the ASEAN Economic Community - เถื่อนนาดี อังศุธร (Journal of Applied Economics and Management Strategy, 2018)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาความต้องการแรงงานในเชิงคุณภาพของสถานประกอบการภาคอุตสาหกรรมในจังหวัดชลบุรี เพื่อให้สอดรับกับการพัฒนาศักยภาพทรัพยากรมนุษย์เพื่อรองรับการเปิดเสรีประชาคมเศรษฐกิจอาเซียนมีวิธีการศึกษาเชิงพรรณนา โดยการวิจัยจากเอกสารและจากการสำรวจภาคสนามด้วยวิธีการสัมภาษณ์เชิงลึกและสัมภาษณ์ตรง กลุ่มตัวอย่างคือสถานประกอบการอุตสาหกรรมในจังหวัดชลบุรี จำนวน 330 สถานประกอบการ จำแนกตามกลุ่มอุตสาหกรรมและขนาดของอุตสาหกรรม เครื่องมือที่ใช้ในการศึกษาคือแบบสัมภาษณ์และแบบสอบถาม ครอบคลุมเนื้อหา 1) ประเด็นปัญหาคุณภาพแรงงาน 2) ความต้องการแรงงานเชิงคุณภาพในปี พ.ศ. 2557 โดยการประเมินสมรรถนะการทำงานของแรงงานในสถานประกอบการ3 ด้าน คือ ความรู้ ทักษะ และคุณลักษณะ เพื่อวิเคราะห์ช่องว่างของระดับสมรรถนะของแรงงานซึ่งจำแนกตามทักษะฝีมือ และกลุ่มอาชีพและ 3) การวิเคราะห์ความต้องการของสถานประกอบการต่อการพัฒนาคุณภาพของแรงงานไทย เมื่อมีการเปิดเสรีประชาคมเศรษฐกิจอาเซียน ผลการศึกษาในประเด็นที่หนึ่งพบว่า สถานประกอบการในจังหวัดชลบุรีส่วนใหญ่พบปัญหาคุณภาพแรงงานโดยมีปัญหาคุณภาพด้านทักษะมากที่สุด รองลงมาได้แก่ปัญหาด้านคุณลักษณะและความรู้ตามลำดับ และตลาดแรงงานในจังหวัดชลบุรีพบสภาวะการสมัครงานต่ำกว่าวุฒิถึงร้อยละ 23.68 สะท้อนถึงความไม่สอดคล้องกันระหว่างอุปสงค์และอุปทาน เกิดความไม่สอดคล้องกันในแนวดิ่ง (Vertical Mismatch) และปัญหาการว่างงานแอบแฝงขึ้น ผลการศึกษาในประเด็นที่สองการวิเคราะห์ความต้องการแรงงานคนในเชิงคุณภาพโดยวิเคราะห์ช่องว่างสมรรถนะ (Competency Gap) ซึ่งเป็นสมรรถนะหลัก (Core Competency) ในการทำงานของแรงงานจำแนกตามทักษะฝีมือของแรงงาน พบว่า แรงงานกลุ่มมีฝีมือมีช่องว่างสมรรถนะด้านภาษาต่างประเทศมากที่สุด กลุ่มแรงงานกึ่งฝีมือ มีช่องว่างสมรรถนะด้านคอมพิวเตอร์มากที่สุด ส่วนกลุ่มแรงงานไร้ฝีมือ พบว่า มีช่องว่างสมรรถนะด้านภาษาต่างประเทศมากที่สุด ผลการศึกษาประเด็นที่สาม ความต้องการของสถานประกอบการต่อการพัฒนาคุณภาพแรงงานไทยเมื่อมีการเปิดเสรีประชาคมเศรษฐกิจอาเซียน พบว่าสถานประกอบการมีความต้องการให้แรงงานไทยมีการพัฒนาสมรรถนะด้านทักษะมาเป็นอันดับแรก โดยเฉพาะทักษะด้านภาษาต่างประเทศ ความชำนาญเฉพาะงาน การคิดวิเคราะห์อย่างมีเหตุผลและการแก้ไขปัญหาเฉพาะหน้า และด้านคอมพิวเตอร์ เป็นต้นสมรรถนะอันดับที่สอง ได้แก่ ด้านคุณลักษณะ โดยเฉพาะคุณลักษณะด้านความขยันอดทนและตรงต่อเวลา ความกระตือรือร้นในการทำงาน ความรับผิดชอบและความเป็นผู้นำ เป็นต้นสมรรถนะอันดับสุดท้ายที่สถานประกอบการมีความต้องการให้แรงงานไทยมีการพัฒนา คือด้านความรู้ โดยเฉพาะความรู้เรื่องภาษาต่างประเทศคอมพิวเตอร์ วิศวกรรม เทคโนโลยี การช่าง เรื่องอุตสาหกรรมและมาตรฐานอุตสาหกรรม เป็นต้น This research aims to study the qualitative labor demand of industrial companies in Chonburi Province related to human resource development for supporting AEC liberalization. The research was conducted in the form of descriptive research through documentary research and field survey conducted by using in-depth interview and direct interview. The sample group was 330 industrial companies in Chonburi Province classified by industrial groups and industrial sizes. Tools used in this research were interview form and questionnaire form with the content covering: 1) issue on labor quality; 2) qualitative labor demands in 2014 by evaluating working competency of labors in places of business regarding three dimensions including knowledge, skills, and attribute for analyzing competency gap level of labors classified by their skills and occupational groups; and 3) analysis on demands of industrial companies regarding Thai labor development towards AEC integration. The results of the 1st issue showed that most places of business in Chonburi Province had encountered with the foremost problems on labor quality and labor skills competency and followed by problems on attribute and knowledge competency, respectively. In addition, labor market in Chonburi Province was facing with the situation of under-qualified employment at 23.68% reflecting inconsistency between demand and supply resulting in Vertical Mismatch and the problem on disguised unemployment. For the results of the 2nd issue regarding analysis on qualitative labor demands by analyzing on competency gap that was the core competency of labor’s working classified upon labor skills, it was found that skilled labors had the highest level of competency gap on foreign languages while semi-skilled labors had the highest competency gap on computer. Finally, unskilled labors had the highest level of competency gap on foreign languages and skill for specific job. The results of the 3rd issue on demands of industrial companies on Thai labors development towards AEC, it was found that places of business demanded Thai labors with skills as the first rank, especially skills on foreign languages, specific skills, analytical skills, ad hoc situation problem solving, and computer, etc. The second rank of competency required by industrial companies was attribute, especially attribute on diligence, patience, being punctual and enthusiastic in working, responsibility, and leadership, etc. The last competency demanded by places of business was knowledge, especially knowledge on foreign languages, computer, engineering, technology, technician, industry, and industrial standards, etc.